Search for CP violation in τ → ππ0ντ decay - Avery, P; Prescott, C; Rubiera, A; Stoeck, H; Yelton, J; Brandenburg, G; Ershov, A; Kim, D; Wilson, R; Bergfeld, T; Eisenstein, B; Ernst, J; et al. (2001)
We search for CP nonconservation in the decays of τ leptons produced via e+e- annihilation at √s ∼ 10.6 GeV. The method uses correlated decays of pairs of τ leptons, each decaying to the ππ0ντ final state. The search is done within the framework of a model with a scalar boson exchange. In an analysis of a data sample corresponding to 12.2×106 produced τ pairs collected with the CLEO detector, we find no evidence of violation of CP symmetry. We obtain a limit on the imaginary part of the coupling constant parametrizing the relative contribution of diagrams that would lead to CP violation to be -0.046